Nurses\' Compliance with Standard Precautions Based on Health Belief Model in Emergency Departments - Ahdieh Mehravar; Nasrin Mokhtari Lakeh; Abdolhossien Emami Sigaroudi; Saman Maroufizadeh (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Nurses' compliance with standard precautions is a viable tool for decreasing health hazards in health centers. Objective: This study aimed to identify factors affecting compliance with standard precautions (SPs) of infection control based on the health belief model (HBM) among emergency department nurses employed in the educational-therapeutic centers affiliated with Guilan University Medical Sciences in Rasht City, Iran. Materials and Methods: This cross-sectional study included 252 nurses working in the emergency departments of hospitals in Rasht City. The study samples were recruited using the convenience sampling method from September to October 2020. Nurses completed questionnaires, including demographics data, HBM constructs, knowledge, and compliance with standard precautions. A hierarchical multiple linear regression analysis was used to identify factors related to compliance with SPs. Results: The mean ±SD age of the nurses was 32.77±7.05 years, and the majority of them were females (88.9%). Their mean ±SD score for compliance with SPs was 63.2 ±16.0 (out of 100). The multivariable analysis results showed that the knowledge (β=0.47, 95%CI; 0.30-0.64, P=0.001), perceived benefits (β =0.19, 95%CI; 0.03-0.36, P=0.022) and perceived susceptibility (β =0.25, 95%CI; 0.13-0.36, P=0.001) constructs of HBM were positively correlated with the compliance with SPs. Furthermore, the level of education was significantly related to the compliance with SPs (β =9.51, 95%CI; 0.02-18.99, P=0.049). The final model accounted for 39.8% of the variance in compliance with SPs. Conclusion:  Results indicated improvement in activity and safety level of the healthcare workers and also an increase in the overall level of compliance among nurses through education, regular training, and use of encouragement and punishment policies. It is suggested to follow the World Health Organization protocols. Also, the support management could have a better effect on perceived benefits and cues to action.